Distance learning of financial accounting: Mature undergraduate students' perceptions - Isabel Maldonado; Ana Paula Silva; Miguel Magalh\~aes; Carlos Pinho; Manuel Sousa Pereira; Lígia Torre (Administrative Sciences, 2023)
This research sought to explore self-reported satisfaction levels of mature students enrolled in the virtual financial accounting course of the first online-only bachelor's degree in Portugal. While doing so, it attempted to generate understanding of which factors may affect undergraduate mature students' engagement-herein measured in terms of overall satisfaction-with online learning, particularly, of financial accounting. Thereby, this research addresses several research gaps. First, unlike most recent empirical research, it provides evidence from a post-pandemic period, in 2022. Second, responding to calls for further education research in different contexts, Portugal poses a highly relevant, unexplored research setting since it was only in 2019 that the Portuguese government approved a legal regime to frame distance education at Higher Education Institutions (HEIs). Third, this research focuses on the overlooked, and yet growing, population of adult mature students. The research evidence emerges from 32 valid responses to a structured electronic questionnaire circulated to students at the end of a financial accounting module (in July 2022). Satisfaction rates from students' own perspectives were derived in terms of (i) overall satisfaction, (ii) learning outcomes, (iii) e-learning process, and (iv) pedagogical practices adopted. The assessment of satisfaction levels was determined through Likert-type items with responses ranging from a minimum score of 1 to the highest score of 5. Data gathered were subject to quantitative analysis: descriptive statistics, Pearson correlations, statistical tests, principal component analysis, and linear regression. High levels of satisfaction with distance education were uncovered. We found that pedagogical practices constitute the dimension that contributed the least (though, still importantly) to overall satisfaction as compared with learning outcomes and e-learning process. The results of this research offer the potential to contribute to the implementation of training offerings of online courses at other Portuguese HEIs as well as abroad.
Keywords: 350; distance education; financial accounting education; higher education; online teaching and learning; student perceptions; student satisfaction